2016
DOI: 10.1016/j.oregeorev.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Petrography, mineral chemistry, fluid inclusion microthermometry and Re–Os geochronology of the Küre volcanogenic massive sulfide deposit (Central Pontides, Northern Turkey)

Abstract: Citation for published item:ek ulutD wF nd yym nD F nd gi ekD wF nd el yD hF nd ¤ yzgen D sF nd ok erD wF @PHITA 9 etrogr phyD miner l hemistryD )uid in lusion mi rothermometry nd e!ys geo hronology of the u¤ ure vol nogeni m ssive sul(de deposit @gentr l ontidesD xorthern urkeyAF9D yre geology reviewsF F ppF IEIVF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In fact, Re-Os isochron ages with large MSWD (4-17) for pyrite, chalcopyrite and sphalerite have been previously reported (e.g. Lawley et al, 2013;Akbulut et al, 2016).…”
Section: Resultsmentioning
confidence: 88%
“…In fact, Re-Os isochron ages with large MSWD (4-17) for pyrite, chalcopyrite and sphalerite have been previously reported (e.g. Lawley et al, 2013;Akbulut et al, 2016).…”
Section: Resultsmentioning
confidence: 88%
“…For this reason, more detailed mapping studies should be done and associated with these regions. In addition, there are Cyprus type and Besshi type massive sulphide mineralizations associated with mafic tholeiitic volcanism, metavolcaniclastics and metaclastics also there are arc-back arc geochemical signatures in the Central Pontides (Çakır, 1995;Altun et al, 2015;Çimen et al, 2016;Akbulut et al, 2016;Günay et al, 2018Günay et al, , 2019Yalçın, 2018).…”
Section: Thementioning
confidence: 99%
“…The Küre volcanogenic massive sulphide (VMS) Cu deposit (Kastamonu), established in the Central Pontides is held in the Cyprus type (Ustaömer and Robertson, 1994;Çakır, 1995;Altun et al, 2015;Akbulut et al, 2016) or Besshi type (Koç et al, 1995). Another VMS deposit is located 54 km north of the study area was observed within the metamorphic rocks in Çangaldağ complex (Dönmez et al, 2013;Günay et al, 2018).…”
Section: Geologymentioning
confidence: 99%